BRAND IMAGE, PROMOSI, DAN KEPUTUSAN PENDENGAR (Studi pada PT. Radio Praja Media Swara (Prameswara) FM 103,9 MHZ Lamongan) - Kholis, M Nur; Lailiyah, Elliv Hidayatullah; Sawabi, Sawabi (Universitas Muhammadiyah Parepare, 2021)
Radio is one of the mass media that can be used to disseminate various kinds of information as well as for entertainment. Currently, many radio stations have been established so that each radio station is competing to disseminate a variety of interesting and worthy information to be sold to the public. One way to achieve a sustainable competitive advantage is to establish a good brand image. Equally important for the world of broadcasting is the promotion that broadcasters can do to stay afloat. A strong brand image and promotion that is widely recognized by consumers is a long-term investment for the company. This study aims to determine the effect of brand image and promotion on listener decisions at Radio Prameswara FM 103.9 MHZ Lamongan. This study uses a survey method with data collection using questionnaires and interviews. The data analysis technique used multiple linear regression. The results showed that brand image had a positive effect on listeners' decisions. If the brand image is implemented better, it will improve listeners' decisions in choosing radio broadcasting institutions. The promotion has a positive effect on the listener's decision. The existence of good product promotion will influence listeners' thinking and convince listeners in choosing the products offered by radio broadcasters. Â